A case of non-Fanconi anemia bone marrow dysfunction with familial involvement - Papadopoulos, N. G.; Papadaki, E.; Kitsiou-Tzeli, S.; Farmakakis, T.; Fretzayas, A. (Pediatr Hematol Oncol, 1998)
We report on a Greek girl with pancytopenia, short stature, clinodactyly, cleft palate, exopthalmus, strabismus, café-au-lait spots, and mild mental retardation in whom chromosomal analysis excluded Fanconi anemia. The occurrence of erythroleukemia in the family and the presence of macrocytosis in her father and low blood counts in her sister favor the diagnosis of an inherited syndrome of familial marrow dysfunction rather than that of a sporadic case.
Keywords: Abnormalities; Multiple Anemia Bone Marrow Diseases Child; Preschool Female Humans Syndrome